Efecto de los tratamientos del suelo sobre la regeneración natural en un bosque secundario - Granados Loarca, José Nicolás; Hutchinson, Ian; Ferreira, Pedro; Finegan, Bryan; Martín, P. (CATIE, 2015)
This study was carried out in a natural secondary forest at Pilar de Cajón, Pérez Zeledón, Costa Rica. It compared the effects on natural regeneration (though consequences for seed dispersal, germination and seedling establishment) of silvicultural tratments of the understorey and the soil surface, including the ranking oof of leaf litter and prescribed burning. The study lasted for 5 months, starting in March 1995 and finishing in July of the same year. Experimental results indicated that prescribed burning had a marked positive effect on the natural regeneration of valuable species, creating conditions superior to those of both raked plots and untreated control plots.